2017
DOI: 10.1136/bcr-2017-220196
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent tackle: a novel surgical approach to a rugby-related jejunal perforation

Abstract: Viscus perforation in the context of blunt-force abdominal trauma is a rarity. Within a sporting context, it is especially rare. However, the increasing physicality observed in rugby union, both in the amateur and professional setting, has resulted in a higher rate of serious injury. We report a novel laparoscopic surgical approach to the management of a traumatic jejunal perforation sustained on the playing field in a previously fit and healthy 28-year-old.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Small bowel injury in a sports setting is a rare occurrence with a paucity of reported cases. Up to 2017, only seven cases had reported jejunal perforation resulting from sports activities [3]. This case is a show to improve the safety in sport and Physician concern more and more for abdominal traumas.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Small bowel injury in a sports setting is a rare occurrence with a paucity of reported cases. Up to 2017, only seven cases had reported jejunal perforation resulting from sports activities [3]. This case is a show to improve the safety in sport and Physician concern more and more for abdominal traumas.…”
Section: Introductionmentioning
confidence: 85%
“…There is some debate in the literature on the mechanism of small bowel injury due to blunt trauma. Three mechanisms are commonly discussed: shear forces, compression between the abdominal wall and the spine, and burst injury due to a sudden increase in Intraluminal pressure [3][4][5][6]. Full-thickness perforations due to rupture forces are most common in the small intestine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Small bowel perforation is an infrequent injury following blunt abdominal trauma and it is rarely reported in a sporting context [1]. A large prospective multi-institutional study on blunt abdominal trauma found that perforating small bowel injury accounted for less than 0.3% of cases.…”
Section: Dear Editormentioning
confidence: 99%
“…Intra-anal fistulotomy with marsupialization for recurrent high intersphincteric fistulaa video vignette doi:10.1111/codi.15071 Dear Editor, Anal fistulas are classified according to their anatomic relationship to the anal sphincter [1]. The internal opening lies at the dentate line: submucosal, runs under the anoderm or the rectal mucosa; intersphincteric, crosses the internal sphincter and reaches the skin; transsphincteric, crosses both sphincters; and suprasphincteric extends above the sphincter complex.…”
Section: Correspondencementioning
confidence: 99%